Fungal mycotoxins in food commodities: present status and future concerns - Pandey, Abhay K.; Samota, Mahesh K.; Kumar, Abhishek; Silva, Ana Sanches; Dubey, Nawal K. (Frontiers in Sustainable Food Systems, 2023)
Mycotoxins are toxic secondary metabolites produced by fungi when they colonies the foodstuffs. These are potent toxins having severe health consequences in people, being mutagenic, teratogenic, and carcinogenic. In agricultural commodities, the contamination of mycotoxins is more prevalent. Several fungi can produce mycotoxins on agricultural products during harvest or in postharvest, and they have significant adverse effects on both animal and human beings. The most prevalent mycotoxins found in food commodities are aflatoxins and ochratoxins produced by Aspergillus species, ochratoxins and patulin produced by Penicillium, as well as fumonisins, deoxynivalenol, and zearalenone produced by Fusarium species. Worldwide, fumonisins, patulin, aflatoxins, and ochratoxins, among others, are responsible for numerous acute and chronic diseases in people and domestic animals. In food commodities, mycotoxins have been quantified and detected using various analytical methods. Besides, mycotoxins occurrence in food commodities were decontaminated through many potential approaches, such as physical, chemical, and biological methods. This review summarizes the findings of 30 years of research into mycotoxins in major commercial food crops including wheat, maize, sorghum, pearl millet, peanut, oat, pulses, barley, oilseeds, rice, and fruits and fruit juices. We also discuss the detection methods of major mycotoxins, available decontamination strategies along with their disadvantages and knowledge gaps. It is anticipated that data from meticulous studies on mycotoxins in food commodities will help in the development of safer food and in setting priorities for future research.